RNA epitranscriptomics: Regulation of infection of RNA and DNA viruses by N6‐methyladenosine (m6A). (26th April 2018) - Tan, Brandon; Gao, Shou‐Jiang
Summary: N 6 ‐methyladenosine (m 6 A) was discovered 4 decades ago. However, the functions of m 6 A and the cellular machinery that regulates its changes have just been revealed in the last few years. m 6 A is an abundant internal mRNA modification on cellular RNA and is implicated in diverse cellular functions. Recent works have demonstrated the presence of m 6 A in the genomes of RNA viruses and transcripts of a DNA virus with either a proviral or antiviral role. Here, we first summarize what is known about the m 6 A "writers, " "erasers, " "readers, " and "antireaders" as well as the role of m 6 A in mRNA metabolism. We then review how the replications of numerous viruses are enhanced and restricted by m 6 A with emphasis on the oncogenic DNA virus, Kaposi sarcoma–associated herpesvirus (KSHV), whose m 6 A epitranscriptome was recently mapped. In the context of KSHV, m 6 A and the reader protein YTHDF2 acts as an antiviral mechanism during viral lytic replication. During viral latency, KSHV alters m 6 A on genes that are implicated in cellular transformation and viral latency. Lastly, we discuss future studies that are important to further delineate the functions of m 6 A in KSHV latent and lytic replication and KSHV‐induced oncogenesis.